The Oxford handbook of the Latin Bible - Houghton, H. A. G. (Oxford handbooks, 2023)
The Oxford Handbook of the Latin Bible contains thirty-one chapters covering the history of the Latin Bible from its earliest translations (the Vetus Latina), the revisions leading to the Vulgate, the achievements and innovations of the Carolingian period and Middle Ages, the development of modern scholarship, and the twentieth-century innovation of the Nova Vulgata. It includes discussions of key figures and interpreters, the most important manuscripts, and the significance of the Latin Bible in multiple fields.